2003
DOI: 10.1103/physrevd.68.093012
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on the mass of thebquark, reexamined

Abstract: Recent results from the DELPHI Collaboration led us to review the present bounds on the bЈ quark mass. We use all available experimental data for m b Ј Ͼ96 GeV to constrain the bЈ quark mass as a function of the Cabibbo-Kobayashi-Maskawa elements in a sequential four generation model. We find that there is still room for a bЈ with a mass larger than 96 GeV.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Theoretical constraints like the perturbativity of the Yukawa couplings and the perturbative unitarity of heavy fermion scattering amplitudes [17] bound the masses from above. In spite of the rather strong bounds from all the above directions, there is still parameter space available for the fourth generation that is consistent with all the data [18][19][20][21][22][23][24][25][26][27][28][29]. The fourth-generation scenario (SM4) is thus still viable even after the recent Tevatron and LHC results [30,31].…”
Section: Introductionmentioning
confidence: 90%
“…Theoretical constraints like the perturbativity of the Yukawa couplings and the perturbative unitarity of heavy fermion scattering amplitudes [17] bound the masses from above. In spite of the rather strong bounds from all the above directions, there is still parameter space available for the fourth generation that is consistent with all the data [18][19][20][21][22][23][24][25][26][27][28][29]. The fourth-generation scenario (SM4) is thus still viable even after the recent Tevatron and LHC results [30,31].…”
Section: Introductionmentioning
confidence: 90%
“…The corresponding lower bounds are m t ′ > ∼ 220 and m b ′ > ∼ 190 GeV [30]. The above limits can be relaxed if we consider the possibility that b ′ → bH , b ′ → cW and b ′ → bZ decays can be of comparable size under certain conditions of the CKM elements [31,32]. Unless associated CKM elements are extremely small, in general the b ′ (and certainly the t ′ ) quark should not be very long-lived.…”
Section: Direct Searchmentioning
confidence: 99%
“…Searching for b ′ quark through its FCNC decays, an analysis by D0 excludes the b ′ in the mass range M Z /2 < m b ′ < M Z +m b that decays via the FCNC b ′ → bγ process [27]. CDF excludes [28] The above limits can be relaxed if we consider the possibility that b ′ → bH , b ′ → cW and b ′ → bZ decays can be of comparable size under certain conditions of the CKM elements [31,32]. Unless associated CKM elements are extremely small, in general the b ′ (and certainly the t ′ ) quark should not be very long-lived.…”
Section: Direct Searchmentioning
confidence: 99%
“…If a priori assumptions on b decays are not made, limits can be found on the branching ratios of these two channels [407][408][409]. In particular, it is found that for b quarks with masses ∼100 GeV near the LEP kinematical limit there are some windows in parameter space where b could have escaped discovery.…”
Section: New Quarksmentioning
confidence: 99%